KRISTIJONAS DONELAITIS AND HIS CONTEMPORARIES. THE REGISTER OF BAPTISMS OF THE PARISH OF TOLLMINGKEHMEN FROM 1725 TO 1754 AS AN (AUTO-) BIOGRAPHICAL SOURCE - SCHILLER, CHRISTIANE (Knygotyra, 2015)
This article focuses on the register of baptisms of the parish of Tollmingkehmen from 1725 to 1754, which has survived on a single microfilm housed at Deutsche Zentralstelle fur Genealogie at the State Archive Leipzig. The analysis of this register revealed that the excerpts made by Franz Tetzner in the end of the 19th century are far from being complete. Since Tetzner excerpted only passages with respect to his own interests, details on Donelaitis’ life and his moral values, whichcan be gained from Tetzner, are quite fragmentary and often ambiguous. In order to interpret the entries and addenda made by Donelaitis correctly they must be viewed in a broader context, i.e. with regard to the common practice of recording baptisms in Prussia and in comparison to those recorded by Donelaitis’ predecessors. The recent, albeit superficial analysis of the register of baptisms of the parish of Tollmingkehmen not only sheds light on the social relations of Donelaitis with his parishioners and colleagues, among them Philipp Ruhig, but also offers valuable information about the colleagues themselves. Therefore, all passages neglected by Tetzner should be subject of further investigation. They may reveal more hitherto unknown facts about Kristijonas Donelaitis’ life and moral values.